La guerre et les rites de guerre dans le judaïsme du deuxième Temple - Batsch, Christophe (Supplements to the Journal for the Study of Judaism, 2005)
This work deals with the Jewish warfare in the Hellenistic and Roman Antiquity from the point of view of the religious rites which, for the Ancients, were a necessary part of all social activity. The author rejects the traditional concept of "Holy War" and prefers to emphasise the diversity of representations of war in the Judaism of the Second Temple. The book deals with questions linked to the status of warriors and priests who were involved in war with regard to purity laws. It analyses the rituals specific to military operations. It deals with the Sabbath, with the war oracle of the ourim and toummim as well as the different types of sacrifices associated with war. The book presents a comprehensive but diverse and contrasted portrait of the Jewish practises and representations of war in Ancient times.